The Effect of Oxygen Inhalation Therapy on Hemodynamics (Heart Rate and Respiratory Rate) in Toddlers With Pneumonia - Tri Imroatun; Nyimas Heny Purwati; Anita Apriliawati; Titin Sutini (UIMA Press, 2023)
Background: Pneumonia causes the lung tissue to become inflamed, the alveoli are filled with pus and fluid causes difficulty in oxygen absorption resulting in difficulty breathing. Children with pneumonia cause the ability of the lungs to expand to decrease so that the body reacts by breathing quickly so that hypoxia does not occur. Objectives: The purpose of this study was to determine the effect of inhalation therapy using oxygen on hemodynamics (Heart Rate and Respiratory Rate) in children under five with pneumonia. Methods: The design of this study was a quasy experiment with the control group and the intervention group, the number of respondents in this study was 32 respondents who were divided into two groups, the sampling used was a simple random sampling method. Results: The results showed that the mean heart rate value of the intervention group compared to the control group was 131.29;135.04, in addition to that the mean respiratory rate value of the intervention group and control group was 32.01;34.20. from the results of the bivariate analysis it was found that there was an influence before and after in the control group and the intervention group with p-value=0.000. Conclusion: the conclusion in this study is So, from the results of this study, researchers argue, in providing respiratory rate stability to pediatric patients with respiratory tract disorders such as pneumonia, both therapies can be given, both inhalation therapy with oxygen, and inhalation therapy using compressors.